TEACHING LISTENING AND SPEAKING - Nizomiddin, Ma’sudov (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2023)
Knowing English involves not only producing the language correctly, but also using it for particular purposes. Fraser (in Richards, 1983:30) states that when people use language, they characteristically do three things: they say something, they indicate how they intend the hearer to take what they said, and they have definite effects on the hearer results. In this context, it can be said that language means something spoken. People usually speak or share their opinion with one another by using it.